The Randomized Clinical Trial of Pentoxifylline for Reduction of Blood Pressure in Patients with Primary Hypertension - Hossein Namdar; Sajad Khiali; Naser Khezerlou Aghdam; Afshin Gharekhani; Taher Entezari-Maleki (Tabriz University of Medical Sciences, 2020)
Background: Pentoxifylline (PTX) is a xanthine derivative with the potential cardiovascular effects. This study was done to evaluate the impact of pentoxifylline on blood pressure when added to patients' antihypertensive regimen. Methods: A randomized control trial were carried out on 100 patients with primary hypertension for a three-month period. The intervention group received 1200 mg daily PTX in three divided doses plus the standard treatment of antihypertensive medications, whereas the control group received only the standard treatment of hypertension. Patients' blood pressure was measured at baseline, 4, and 12 weeks after intervention. Patients were also followed up for major adverse cardiac events. Results: After 4 weeks and 12 weeks of study, no significant difference was observed in systolic blood pressure (SBP) (135 ± 16 vs. 136.2 ± 17.2 mmHg, p=.72; 134.8 ± 13.3 vs. 134.3 ± 14.7 mmHg, p=.85) and diastolic blood pressure (DBP) (81.5 ± 9.9 vs. 82.4 ± 12.9 mmHg, p=.69; 80.8 ± 9 vs. 80.4 ± 10.7 mmHg, p=.84) between two groups. Conclusion: The result showed that PTX has not a significant effect on BP in patients with primary hypertension.